Fatal rhabdomyolysis after acute sodium monensin (Rumensin®) toxicity: case report Rabdomiólise fatal aguda pós-intoxicação por monensina sódica (Rumensin®): relato de caso - João Aris Kouyoumdjian; Maria da Penha Ananias Morita; Adriana Komatsu Sato; Amalia Fernanda Pissolatti (Arquivos de Neuro-Psiquiatria)
Myoglobinuria or rhabdomyolysis occurs when myoglobin escapes into the blood and then into the urine after acute muscle necrosis. It can be a serious medical condition leading to renal failure and death. There are many causes including exertion, crush syndromes, ischaemia, metabolic disorders, exogenous toxins and drugs, heat stroke and hereditary disorders such as malignant hyperthermia. We report the case of a 17 year-old boy who developed myoglobinuria, renal failure and death 11 days after ingesting sodium monensin, possibly with the intention of developing muscles. Sodium monensin, the active principle of Rumensin®, is a dietary additive used as a growth promoter for confined cattle. There are no previous reports of human intoxication. Accidental or experimental sodium monensin intoxication in animals produces similar findings to those seen in this case. Mioglobinúria ou rabdomiólise refere-se a necrose muscular aguda com liberação de mioglobina na circulação e na urina podendo causar, na sua forma mais grave, insuficiência renal e óbito. A etiologia é ampla, incluindo exercício intenso, síndrome do esmagamento, isquemia, toxinas exógenas, anormalidades metabólicas, medicações, altas temperaturas, além de algumas condições herdadas como hipertermia maligna. Neste relato descreve-se o caso de um paciente jovem, do sexo masculino, que desenvolveu mioglobinúria, insuficiência renal e óbito, 11 dias após ingestão de monensina sódica, princípio ativo de Rumensin®, usado como aditivo alimentar para gado confinado; a ingestão possivelmente foi feita para desenvolvimento muscular. Não há relato na literatura de intoxicação humana e o quadro clínico nos animais com intoxicação experimental ou acidental pelo Rumensin® se assemelha àquele observado no presente caso.